EVA (Early Vascular Aging) – Übersetzung in den klinischen Alltag - Middeke, Martin (DMW - Deutsche Medizinische Wochenschrift, 2019)
Early Vascular Aging, a concept describing pathophysiologic and clinical aspects of premature arterial stiffness and arteriosclerosis, has attracted attention in recent years. Early diagnosis and intervention is essential for prevention and postponing cardiovascular events.
Keywords: vaskuläres Altern; arterielle Gefäßsteifigkeit; primordiale Prävention